Efficiency of Managing a Stochastic Inventory System in a Declining Market for Non-Instantaneous Deteriorating Items under Partial Backlogs - Keswani, Mamta; Dwivedi, Vinita; Kumar, Lalji; Kumar, Bhupendra; Khedlekar, Uttam Kumar (Yugoslav Journal of Operations Research; Vol 35 No 3 (2025), 2024)
In a declining market, companies must adapt their strategies during the mature stage to maintain competitiveness. One of the effective approach to sustaining demand is through targeted promotional efforts, which can extend the products demand in the market. Additionally, implementing an appropriate pricing strategy is essential to ensure products are sold before its start deteriorate or the season ends. This paper explores the role of promotional efforts in shaping pricing policies for non-instantaneous deteriorating items in the declining demand scenario. In the model, we consider the demand as a function of both price and time, incorporating assumptions of partial backlogging for shortages, losts sales, fixed holding costs, and deterioration rate. Using these assumptions, we develop an inventory model that starts with a shortage and ends with zero inventory. The objective is to maximize expected profit per unit time by optimizing both the selling price and replenishment schedules. The innovation of this study lies in integrating promotional efforts with pricing strategies, specifically designed for deteriorating items in a declining market. We present a numerical example to demonstrate the model’s effectiveness and conduct a sensitivity analysis to examine its performance under varying conditions. Finally, we provide managerial insights and outline potential directions for future research.